2015
DOI: 10.1016/j.myc.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic identity of a Phakopsora fungus causing the grapevine leaf rust disease in Southeast Asia and Australasia

Abstract: Morphology Phylogeny Pucciniales Vitaceae a b s t r a c t Three distinct groups were revealed among the grapevine leaf rust fungi from Japan, Taiwan, Thailand, Malaysia, Indonesia, East Timor and Australia in phylograms generated from sequence analyses of the internal transcribed spacer 2 and the large-subunit rRNA gene (D1/D2 region). A group of Thai, Malaysian-Indonesian and East Timorese-Australian fungi was distinct from two other groups of grapevine leaf rust fungi, Phakopsora meliosmaemyrianthae and P. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…[61] 2014 Australasia and Southeast Asia Grapevine P. montana Leaf rust Angular brown spots on the topside of the leaf. [62] 2015 USA…”
Section: Erwinia Amylovoramentioning
confidence: 99%
“…[61] 2014 Australasia and Southeast Asia Grapevine P. montana Leaf rust Angular brown spots on the topside of the leaf. [62] 2015 USA…”
Section: Erwinia Amylovoramentioning
confidence: 99%
“…Because these specimens were also not available for study, their taxonomic identity was not determined. Unless the presence of teliospores is confirmed, the Southeast Asian Phakopsora species on V. vinifera (Pota et al 2015) is easily mistaken as K. vitis.…”
Section: Resultsmentioning
confidence: 99%
“…Based on host range and morphology, Phakopsora montana was distinguished from the new species P. euvitis , the causal agent of Asian grapevine leaf rust. A proposed synanamorph of P. euvitis is P. meliosmae‐myrianthae (Chatasiri & Ono, ; Pota et al ., ). The heteroecious and macrocyclic P. euvitis produces its uredinial‐telial stage on Vitis species and forms spermogonia and aecidia on the tree Meliosma myriantha , belonging to the family Sabiaceae.…”
Section: Taxonomymentioning
confidence: 97%
“…Molecular phylogenetic analyses confirmed the taxonomic distinctness of Phakopsora ampelopsidis , Phakopsora vitis and P. euvitis and placed P. euvitis closer to P. ampelopsidis than to P. vitis (Chatasiri & Ono, ). Recent molecular phylogenetic analyses of grapevine leaf rust fungi from Asia and Australia suggested that there might be another biologically distinct species besides P. euvitis and P. montana (Pota et al ., ).…”
Section: Taxonomymentioning
confidence: 97%